Strong magnetic field-dual-assisted fabrication of heterogeneous sulfide-based hollow nanochain electrodes for high-rate supercapacitors. Issue 34 (15th August 2019) - Yu, Xing; Yu, Jiali; Fautrelle, Yves; Gagnoud, Annie; Ren, Zhongming; Lu, Xionggang; Li, Xi
Abstract : A strong magnetic field was applied twice to synthesize one-dimensional hetero-Zn0.76 Co0.24 S/Co3 S4 /β-CoS1.097 hollow nanochain-based electrodes for high-rate supercapacitors. Abstract : Many sulfide-based supercapacitors suffer from the problem of large capacity and energy attenuation at high rates. To tackle this problem, a strong magnetic field (SMF) was exerted twice during new material synthesis and electrode fabrication. Here, one-dimensional (1D) hetero-Zn0.76 Co0.24 S/Co3 S4 /β-CoS1.097 hollow sphere nanochains (CZ55 S 6T ) were first prepared via a one-step anion-exchange reaction under SMF. The SMF-induced directional growth of paramagnetic Zn0.76 Co0.24 S in the outer shell contributed to the directional assembly of the simultaneously hollowing-out spheres into 1D nanochains based on the Kirkendall effect accelerated by SMF. Physicochemical investigations revealed that SMF endowed CZ55 S 6T with a larger surface area and reduced the loss of active components, especially Zn. The unique 1D hollow nanochain nanostructures contributed to a remarkable rate performance. An oriented CZ55 S 6T nanochains/graphene flake capacitive electrode (CZ55 S 6T /G) with high loading (∼8 mg cm −2 ) was further fabricated using SMF to reduce the path tortuosity. The CZ55 S 6T /G electrode exhibited strikingly enhanced rate capability with 80% capacitance retention (863.8 F g −1 ) and cycling capacitance (705 F g −1 after 5000 cycles) at a high rate of 20 A g −1 . Furthermore, the CZ55 S 6T /G-based asymmetric supercapacitor delivered remarkable energy density of 51.5 W h kg −1 at a large power density of 6811 W kg −1 .